Practice of Human Resource planning in organizations: A study based on organizational performance (KASBIT Business Journal, 2022)
In the consideration of human resource management practices for the planning purpose in organization, it’s the primary and initial stage of any project, services or product lunching. In the current study the HR planning has been examined with the help of previous literature by listing selection, training, working condition and appraisal as independent variable and organizational performance proxies as job satisfaction the dependent variable. The significance of human resource practice in organization related present and previous comprehensive literature has been covered and a self-rated questionnaire has been distributed amongst the organization top level, middle level and lower level managers. Various frameworks (Hassan et al., 2014) considered having direct relation to HR planning practices, and also the techniques to keep and motivate the employees of the organization. One the basis of non-probability convenience sampling techniques 150 participants has been included in the study. After analyzing the two HR planning factors found significant and positive relation job satisfaction and two found insignificant. In conclusion, with are the key for the development of organization, and the most significant factor for the engagement and motivation of employees which further leads to better organizational performance, judged as job satisfaction level. The implication of the study provided a glimpse for the organization planning to strengthen their HR department, by providing training and development opportunities to current employees and also planning on the retaining talented employee’s policies e.g. promotion on merit basis, provide better working environment and incentives.
Keywords: Human Resource Planning; Human Resource Management; Selection; Training; Appraisal; Working Condition; Job Satisfaction